2021
DOI: 10.1016/s2666-7568(21)00212-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the relationships between physiological indicators and all-cause mortality (NHANES): a population-based cohort study

Abstract: Background Mortality risk stratification based on dichotomising a physiological indicator with a cutoff point might not adequately capture increased mortality risk and might not account for non-linear associations. We aimed to characterise the linear and non-linear relationships of 27 physiological indicators with all-cause mortality to evaluate whether the current clinical thresholds are suitable in distinguishing patients at high risk for mortality from those at low risk.Methods For this observational cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…Some items (collection of demographic data and the description of self and family information) may be relatively inaccurate, and there may be ineluctable recall and self‐reporting biases in the process of the overall data collection. Nevertheless, despite this, whole data collection process of NHANES is dependable and trusted, and has been verified by several previous researches 45,46 . Third, due to the different living habits and environments of individuals in different countries and ethnic groups, this study only includes the samples from the NHANES, and subsequent prospective investigations of more nationalities around world is also of great significance in the future.…”
Section: Discussionmentioning
confidence: 82%
“…Some items (collection of demographic data and the description of self and family information) may be relatively inaccurate, and there may be ineluctable recall and self‐reporting biases in the process of the overall data collection. Nevertheless, despite this, whole data collection process of NHANES is dependable and trusted, and has been verified by several previous researches 45,46 . Third, due to the different living habits and environments of individuals in different countries and ethnic groups, this study only includes the samples from the NHANES, and subsequent prospective investigations of more nationalities around world is also of great significance in the future.…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies have also revealed reduced lipoprotein synthesis in hepatocyte cell lines exposed to TNF-α and IL-6 (42); decrease in HDL-C may be also associated with high levels of secreted phospholipase A2 (43) or with the downregulation of phospholipid and cholesterol influx into HDL mediated by ATP-binding cassette transporter-1 in inflammation (44). Low cholesterol has been shown to be associated with the severity of disease progression and poor prognosis in various critical illnesses such as sepsis, heart failure, ischemic stroke, and malignancy (25)(26)(27)(28)(29)(45)(46)(47)(48)(49)(50). A recent study found that patients with severe COVID-19 also had dyslipidemia, characterized by lower HDL-C and TC levels related to disease progression (51).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that HNC is one of the main cancers of focus, the result of this study is consistent with the previous studies. A plausible explanation for these associations may be related to the damage caused by elevated GFR to the capacity of the renal tubules to reabsorb fluids and minerals from urine [ 16 ]. Damaged or destroyed tubules can lead to a common type of kidney injury known as acute tubular necrosis, which has been implicated in kidney failure [ 10 ].…”
Section: Discussionmentioning
confidence: 99%